ARE ENTREPRENEURS BORN OR MADE? A LOOK AT ENTREPRENEURIAL MARKETING EDUCATION WITHIN VOCATIONAL HIGH SCHOOL - Santoso, Adhi Setyo; Haryanto, Jony Oktavian; Widyanto, Hanif; Suryanto, Hari; Rosmawati, Lina (UI Scholars Hub, 2021)
Manuscript Type: Research Article Research Aims: The research studies the contextual stimuli (business knowledge and environment) toward entrepreneurial self-efficacy and locus of control that influence entrepreneurial intention. Design/methodology/approach: The survey involved vocational high school students in Mataram, Nusa Tenggara Barat, Indonesia, and collected 101 responses. The research applies a quantitative method of 2-steps Partial Least Square – Structural Equation Modelling (PLS-SEM). Research Findings: Results confirms that business knowledge influences entrepreneurial intention mediated by entrepreneurial self-efficacy. Environment influences entrepreneurial intention mediated by locus of control only if students participate in entrepreneurial marketing education. Theoretical Contribution/Originality: The findings contributed to entrepreneurship literature by showing the role of entrepreneurial marketing education in enhancing student’s locus of control, which enables student’s environment to determine entrepreneurial intention. Managerial Implications in the Southeast Asian context: Research highlights important, yet, less discussed context regarding young-age entrepreneurial intention in vocational high school level. Research also demonstrates the significance of integrating entrepreneurial marketing education into school’s curriculum or supplementary curriculum. Research limitations and implications: This study is limited to vocational high school student context. Research on a more mature respondent context may produce different result